2022
DOI: 10.1021/acsomega.2c04098
|View full text |Cite
|
Sign up to set email alerts
|

Natural Small-Molecule-Based Carrier-Free Self-Assembly Library Originated from Traditional Chinese Herbal Medicine

Abstract: The carrier-free self-assembly of small molecules opens a new window for the development of nanomaterials. This study is dedicated to developing binary small-molecular self-assemblies derived from phytochemicals in traditional Chinese herbal medicine. Among them, Rhei Radix et Rhizoma and Coptidis Rhizoma are a common pair used in clinics for thousands of years. Here, we found that there were numerous spherical supramolecular nanoparticles (NPs) originated from Rhei Radix et Rhizoma and Coptidis Rhizoma decoct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 73 publications
0
17
0
Order By: Relevance
“…Further, the irregular spherical shape of AA-NPs was also observed in the TEM image (Figure B). In the UV–vis absorption spectrum, a broad peak at 256 nm of AA-NPs was attributed to the π–π* transition of carbon, suggesting the presence of the benzene ring or CC (Figure C) . Interestingly, AA-NPs also possessed a certain fluorescence.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Further, the irregular spherical shape of AA-NPs was also observed in the TEM image (Figure B). In the UV–vis absorption spectrum, a broad peak at 256 nm of AA-NPs was attributed to the π–π* transition of carbon, suggesting the presence of the benzene ring or CC (Figure C) . Interestingly, AA-NPs also possessed a certain fluorescence.…”
Section: Resultsmentioning
confidence: 99%
“…Modern research on herb decoctions should clarify the characteristics of each component and the interaction between them. Gradually, an increasing number of researchers have found that nanoscale particles are ubiquitous in decoctions, which are associated with their pharmacological effects . For example, a colloid system with a size of 162 nm isolated from the codecoction of Glycyrrhiza uralensis Fisch and Coptis chinensis Franch was composed of 34 flavonoids, 34 alkaloids, and 2 triterpenoids, showing stronger antibacterial activity than a noncolloidal solution .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…37,38 Similar results are reported for rhein and coptisine (Rhe-Cop) nanofibers and emodin and coptisine (Emo-Cop) nanoparticles, which form through electrostatic attraction, hydrogen bonding, and p-p stacking. 39 BBR and aristolochic acid can also self-assemble into linear heterogenous supramolecules through electrostatic attraction and p-p stacking, which decreases the toxicity of aristolochic acidinduced acute kidney injury. 40 Single components of CHMs also undergo self-assembly.…”
Section: Nanostructures Of Natural Small Molecules From Chmsmentioning
confidence: 99%